Soluble and Insoluble Dietary Fiber Consumption and Colorectal Cancer Risk: A Systematic Review and Meta-Analysis. (30th June 2022) - Arayici, Mehmet Emin; Mert-Ozupek, Nazli; Yalcin, Femin; Basbinar, Yasemin; Ellidokuz, Hulya
Abstract: Colorectal cancer (CRC) is the third most common cancer worldwide with a high mortality rate. Dietary fibers, both soluble and insoluble, are essential for reducing the risk of CRC. In this study, a meta-analysis was performed to examine the relationship between the soluble and insoluble dietary fiber consumption and CRC risk. The highest vs. lowest fiber concentrations were compared by using PRISMA guidelines. To determine publishing bias, the Egger test; assess study heterogeneity I 2 statistics were used. Studies that reported adjusted relative risk estimates with 95% confidence intervals (Cl) for the associations of interest were included. The results reveal that the relationship between soluble and insoluble fiber intake and the risk of CRC is almost equal [The total fiber ES = 0.75 (95% CI = 0.66–0.86), soluble fiber ES = 0.78 (95% CI = 0.66–0.92), insoluble fiber ES = 0.77 (95% CI = 0.67–0.88)]. Funnel plot and Egger's linear regression tests demonstrated that there was no publication bias. Both soluble and insoluble fiber consumption appear to be protective against CRC, with a clinically significant reduction in CRC risk. It is critical to identify preventive steps to avoid the CRC development, especially by leading a healthier lifestyle that includes healthy diet.